MATHEMATICAL MODELING OF NONMETALLIC PARTICLES MECHANICAL TRAJECTORY IN POURING BOX OF MNLZ - A. N. Chichko; D. M. Kukuj; V. E. Sobolev; S. G. Lihousov; M. E. Kontanistov; V. V. Pivtsaev; A. V. Demin; O. P. Krasjuk (Литьë и металлургия)
The mathematical model for calculations of nonmetallic impurities guidepath in system “steel ladle-pony ladle-crystallizer” is developed. Guidepathes of nonmetallic  particles of  different density, moving from steel ladle into crystallizer, are investigated on the sample of internal cavity of pony ladle of MNLZ RUP “BMZ”.